2004
DOI: 10.1074/jbc.m408123200
|View full text |Cite
|
Sign up to set email alerts
|

A Plasmodium falciparum Dipeptidyl Aminopeptidase I Participates in Vacuolar Hemoglobin Degradation

Abstract: Intraerythrocytic growth of the human malaria parasite Plasmodium falciparum requires the catabolism of large amounts of host cell hemoglobin. Endoproteolytic digestion of hemoglobin to short oligopeptides occurs in an acidic organelle called the food vacuole. How amino acids are generated from these peptides is not well understood. To gain insight into this process, we have studied a plasmodial ortholog of the lysosomal exopeptidase cathepsin C. The plasmodial enzyme dipeptidyl aminopeptidase 1 (DPAP1) was en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
174
0
1

Year Published

2005
2005
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 174 publications
(183 citation statements)
references
References 62 publications
(60 reference statements)
8
174
0
1
Order By: Relevance
“…TgCPC1 and TgCPC2 localize to dense granules (Fig. 8), similar to the localization of P. falciparum cathepsin C, which participates in the breakdown of hemoglobin (6). We showed that inhibition of TgCPC1 and TgCPC2 blocked the breakdown of a marker secreted protein, ␤-lactamase, in the PV (Fig.…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…TgCPC1 and TgCPC2 localize to dense granules (Fig. 8), similar to the localization of P. falciparum cathepsin C, which participates in the breakdown of hemoglobin (6). We showed that inhibition of TgCPC1 and TgCPC2 blocked the breakdown of a marker secreted protein, ␤-lactamase, in the PV (Fig.…”
Section: Discussionmentioning
confidence: 69%
“…Proteinases of Plasmodium appear to facilitate erythrocyte invasion and rupture by degrading cytoskeletal proteins and provide free amino acids by degrading host hemoglobin in food vacuoles. Specific inhibition of the Plasmodium cysteine proteinases causes accumulation of undegraded erythrocyte cytoplasm in the food vacuoles and inhibits multiplication (3)(4)(5)(6).…”
mentioning
confidence: 99%
“…*This Direct Submission article had a prearranged editor. To validate our approach in parasites, we used a potent and irreversible inhibitor of the parasite cysteine protease dipeptidyl aminopeptidase 1 (DPAP1) (23)(24)(25) as our "drug" species. Several factors drove the selection of the DPAP inhibitor ML4118S (24) (herein denoted ML) (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Falcipain-1 (FP1) is much less similar in sequence (38% identity between the catalytic domains of FP1 and FP2), encoded by chromosome 14, and, as determined by recent gene disruption studies, not essential for erythrocytic parasites (16,17). Other putative P. falciparum family C1 proteases (15,18) are three dipeptidyl peptidases, one of which (dipeptidyl peptidase I) was recently characterized as an exopeptidase (19), and nine serine repeat antigens (SERAs), one of which (SERA-5, which has replacement of the catalytic Cys by Ser) was recently shown to have serine protease activity (20).…”
mentioning
confidence: 99%